Design and Analysis of Thermoelectric Dc boost converter - Praveen Kumar Choudhary; Anish Kumar (International Journal of Electro-Mechanics and Material Behaviour, 2026)
In today’s consumer-oriented market, researchers are increasingly focusing on harvesting energy from ambient and renewable sources to enable sustainable power generation and reduce dependency on conventional energy resources such as batteries and fossil-fuel-based electricity. The rapid growth of portable electronics, wireless sensor networks, and Internet of Things (IoT) devices has created a significant demand for low-power, long-life, and maintenance-free energy solutions. In many practical situations, frequent battery replacement is difficult, costly, and environmentally harmful. Therefore, energy harvesting has emerged as an effective alternative to power such low-energy devices by utilizing naturally available energy in the surrounding environment.Energy harvesting methods offer enormous opportunities to derive power from sources such as mechanical vibrations, human motion, thermal gradients, airflow, and other forms of wasted or unused energy. In general, energy harvesters operate like transducers, where the available ambient energy is extracted and converted into usable electrical power. Among different techniques, triboelectric and thermoelectric harvesting are considered highly promising due to their simplicity, compactness, and suitability for small-scale applications.This research aims to demonstrate the practical implementation and performance validation of Thermoelectric Energy Harvesting (THEH) through developed hardware prototypes and experimental setups. A usable amount of electrical energy is extracted from both harvesters under real-world operating conditions. The generated output is measured, analysed, and further validated using the developed hardware model to ensure feasibility for real-time applications. The results indicate that ambient energy harvesting using triboelectric and thermoelectric principles can provide an effective solution for powering low-power electronics and self-sustained sensing systems in future smart applications.
Keywords: Internet of things (IoT); Thermoelectric Dc boost converter; Thermoelectric Energy Harvesting (THEH); renewable energy resources; thermoelectric energy generators